Retrospective study factors related to preterm birth in Government Raja Mirasudar hospital and obstetric and perinatal outcome - Soundarajan, Pradeepa; Muthuramu, Poovathi; Veerapandi, Munira; Mariappan, Rubini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is a leading cause of perinatal mortality and long-term morbidity as well as the long-term health consequences and cognitive outcomes. Present study was conducted to determine prevalence and risk factors and obstetric & perinatal outcome associated with preterm birth in Rajamirasudar Hospital, Thanjavur. Methods: A case control study was conducted between Mar 2015 - Sep 2015 in Rajamirasudar Hospital, Thanjavur. All the live new-borns during the study period were investigated. Of 6805 live births during the study period 356 births occurred in <37 weeks were taken as a case and 579 term neonates were taken as a control group. Data were obtained through review of prenatal and hospital delivery records. Univariate and multivariate logistic regression analysis were applied to obtain magnitude of association between independent variables and preterm birth. Results: The prevalence rate of preterm birth was 5.6%. History of previous preterm birth (OR=12.7,CI: 3.9-40.4, p<0.001), hypertension (OR=7.3, CI: 2.1-25.4, p=0.002), oligohydramnios (OR=3.9, CI:1.6-9.5, p=0.002), diabetics (OR=3.7, CI: 1.1-11.8, p=0.024), premature rupture of membrane (OR=3.1, CI:1.9-4.9, p=0.000), hypothyroid (OR=2.0, CI: 1.0-3.8, p=0.037), prepregnancy low BMI (OR=2.0, CI: 1.1-3.8, p=0.015), urinary tract infection in 26-30 weeks , (OR=1. 8 CI:1.0-3.2, p=0.04) were determined as significant risk factors for preterm birth. Conclusions: Early detection and treatment of diseases or disorders among pregnant women especially hypertension, Oligohydramnios, diabetics, hypothyroid, urinary tract infection, pre pregnancy low BMI as well as the improving health care quality delivered to pregnant women may reduce preterm prevalence rate and also reduce neonatal morbidity and mortality.